Diagnosis of bearing with mechanical vibrations and virtual instruments - Gomez Ramırez, Vıctor Manuel; Serna Bedoya, Juan Carlos; Velez Lopez, Luisa (Visión electrónica, 2014)
The mechanical vibration analysis has great importance in the condition based maintenance; in this sense, the bearings are elements that affect more stops rotating machinery. Therefore, this paper describes the hardware and software architecture of a vibration analyzer developed in LabVIEW oriented to study bearings extracting its parameters or descriptors through the power spectral density (PSD) and the RMS and DC signal values in time. Shows the advantages of working with such solutions: cost and the possibility of increasing benefits as needed.